Female Students' Lived Experiences in the Psychology of Arabic Language Learning: Navigating Challenges, Learner Agency, and AI-Supported Adaptation - Nur Cholis Agus Santoso; Munir Abidin (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The growing adoption of Social–Emotional Learning (SEL) has prompted renewed discussion regarding its compatibility with faith-based educational systems, particularly Islamic Religious Education (IRE), where moral and spiritual values constitute the primary foundation of learning. This study explores how tensions between IRE and SEL emerge and are negotiated within classroom practice. Employing an interpretive qualitative case study, the research was conducted at a private Islamic senior high school in Indonesia involving three Islamic Religious Education teachers, twelve students, and one vice principal selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis and were analyzed using reflexive thematic analysis. The findings reveal that the relationship between IRE and SEL is characterized by continuous epistemological and pedagogical negotiation rather than complete alignment. Religious values remain the dominant framework shaping emotional expression, classroom interaction, and instructional practices, positioning SEL as a complementary rather than autonomous educational approach. Institutional culture, transmissive pedagogy, and ritual-oriented instruction further constrain opportunities for reflective dialogue and authentic socio-emotional development. This study contributes to the literature by proposing the concepts of asymmetrical integration of IRE–SEL and regulated emotionality in religious pedagogy, demonstrating that the implementation of SEL is inherently shaped by religious and cultural contexts. The findings offer practical insights for developing context-sensitive educational policies, curriculum design, and teacher professional development within faith-based schools.